The Effect of Strategic Choices and Management Control Systems on Organizational Performance - Junqueira,Emanuel (2016)
ABSTRACT The study investigates the effect of generic strategic choices and management control systems (MCS) on the organizational performance of large and medium-sized companies located in Espírito Santo, using Contingency Theory as the theoretical framework. It is a quantitative study, using a survey as the data collection technique. 73 questionnaires were validated, after being completed by those responsible for the controlling or related area of these enterprises over the period between February and April of 2014. The data analysis was performed using the structural equations modeling technique. The main results indicate that: (i) competitive forces shape the strategy adopted by the organizations surveyed, however, contrary to what the literature predicts, those companies that operate in more competitive environments choose a strategy of cost leadership instead of differentiation; (ii) the design and use of the MCS is influenced by the strategy chosen, and the use of contemporary management practices is associated with a differentiation strategy; (iii) strategic choices and the MCS have a positive impact on organizational performance. In addition, those companies that combine differentiation strategy with contemporary management practices perform better than the other companies analyzed.